Facile synthesis of polyaniline/titanium carbide (MXene) nanosheets/palladium nanocomposite for efficient electrocatalytic oxidation of methanol for fuel cell application. (1st November 2021) - Elancheziyan, Mari; Eswaran, Muthusankar; Shuck, Christopher E.; Senthilkumar, Sellappan; Elumalai, Satheeshkumar; Dhanusuraman, Ragupathy; Ponnusamy, Vinoth Kumar
Graphical abstract: Highlights: One-step fabrication of MXene nanosheets/polyaniline/palladium nanocomposite electrode. As-prepared electrode showed efficient electrocatalytic oxidation of methanol. PANI/Pd/MXene nanocomposite depicts higher MEOR current density than Pd/MXene. Abstract: Slow methanol oxidation reaction kinetics with current electrocatalysts is the major limitation to widespread application and development in direct-methanol fuel cells (DMFCs). The present work demonstrates a highly efficient electrocatalyst for methanol electrooxidation reaction (MEOR) using polyaniline/palladium/Ti3 C2 T x (PANI/Pd/MXene) nanocomposite. The PANI/Pd/MXene nanocomposite was prepared using a one-pot electrochemical co-deposition technique with a pre-anodized screen-printed electrode (SPE) under acidic electrolyte solution containing Ti3 C2 T x, aniline, and palladium chloride as precursors. The PANI/Pd/MXene nanocomposite was examined using FESEM, TEM, FT-IR, XPS, and cyclic voltammetric techniques. The electrochemical response of the PANI/Pd/MXene nanocomposite shows enhanced electrocatalytic response towards the oxidation of methanol, with a peak current density of 291 mA cm −2, approximately three times higher than Pd/MXene (106 mA cm −2 ). Furthermore, it was also stable up to 100 cycles. The electrochemically active PANI/Pd sites are incorporated with MXene nanosheets, facilitating a more efficient MEOR. This stimulating result was achieved due to the sturdy metal–support interactions between PANI/Pd and MXene nanosheets that provide maximum methanol adsorption on the electrode surface for efficient electrocatalytic oxidation. Thus, the Ti3 C2 T x support tailors the metal electrocatalyst interface and surface properties, resulting in improved electrocatalytic performance. This study highlights a facile approach for designing MXene-supported noble metal electrocatalysts for MEOR in direct-methanol fuel cells.